DAMPAK BUDAYA ORGANISASI DAN MOTIVASI KERJA TERHADAP EFEKTIVITAS KERJA GURU - Nurdin, Nurdin; Zaharuddin, Zaharuddin; Wahyuningsih, Sri (STKIP Pesisir Selatan, 2025)
Motivated teachers will be better able to optimize three key aspects of learning: classroom management, utilization of learning resources, and control of learning dynamics, all of which require effective leadership support. Teachers work effectiveness reflects the quality of educational management, which is shaped not only by systemic structures but also by the internal dynamics of individual educators. This study aims to analyze the impact of organizational culture and work motivation on teacher work effectiveness. In the context of education, these faktors play an important role in improving the performance and productivity of educators. Using quantitative methods, data were collected through questionnaires distributed to teachers in schools in the MTS Ittihadul Mukhlisin Cibinong Bogor West Java area. The results showed that a positive organizational culture contributed significantly to teacher work motivation, which in turn increased their work effectiveness. In addition, high work motivation was proven to be a strong mediator between organizational culture and work effectiveness. These findings provide important implications for education managers in creating a supportive work environment, as well as motivation-enhancing strategies that can maximize teacher performance.